2016
DOI: 10.37828/em.2016.9.7
|View full text |Cite
|
Sign up to set email alerts
|

New Records and Updated Distribution of the Endemic Balkan Rock Lizards Dinarolacerta Spp. In Montenegro

Abstract: This article reports new records and updated distribution of the endemic Balkan rock lizards Dinarolacerta spp. in Montenegro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition to this is also a fact regarding species distribution in Montenegro (e.g. Ljubisavljević et al 2018), as well as a photo from the mentioned study, which clearly shows other lizard species -Algyroides nigropunctatus. Also, in the study among photos, photo of juvenile Pseudopus apodus is wrongly given as Elaphe quatuorlineata.…”
Section: Literature Reviewmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition to this is also a fact regarding species distribution in Montenegro (e.g. Ljubisavljević et al 2018), as well as a photo from the mentioned study, which clearly shows other lizard species -Algyroides nigropunctatus. Also, in the study among photos, photo of juvenile Pseudopus apodus is wrongly given as Elaphe quatuorlineata.…”
Section: Literature Reviewmentioning
confidence: 59%
“…Tomassini (1905) and Fritz (1995) reported presence of Mauremys rivulata along Tivat valley, while preliminary population characteristics of the same species for Tivat valley is given by . Džukić et al (2017) described presence of several species in area of Vrmac hill: Anguis fragilis complex, Hemidactylus turcicus, Algyroides nigropunctatus and Podarcis melisellensis, while Ljubisavljević et al (2018) reported several lizard species: Hemidactylus turcicus, Algyroides nigro-punctatus, Lacerta trilineata, Podarcis melisellensis, Podarcis siculus, Anguis fragilis complex and Pseudopus apodus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Prokletije rock lizard (Dinarolacerta montenegrina) can be expected in the Prokletije massif in the western part of Kosovo and Metohija province (Tomović et al 2014(Tomović et al , 2018 since it is distributed near the border in both Montenegro (Ljubisavljević et al 2007(Ljubisavljević et al , 2014b(Ljubisavljević et al , 2016 and Albania (Petrov 2006, Podnar et al 2014, Mizsei et al 2017. The Greek slow worm (Anguis graeca) occurs in North Macedonia (Jablonski et al 2016(Jablonski et al , 2021, relatively close to the border with Serbia, and its presence can be expected in the extreme southern and south-eastern parts of Serbia (Urošević et al 2020).…”
Section: List Of Amphibian and Reptile Species Of Serbiamentioning
confidence: 99%
“…13). Both species have rather specific habitat requirements [58,59] and therefore restricted distribution within the region [59,60]. Also, local meadow viper populations belong to macrops subclade, as do those from Bosnia and Herzegovina [61].…”
Section: Reptilesmentioning
confidence: 99%